Nadezhda Krupskaya’s contributions to early Soviet adult education theory and practice. - Kate Antanovich; Esther Prins (Adult Education Research Conference, 2023)
This article examines Nadezhda Krupskaya’s contribution to early Soviet adult education, outlines key principles of her adult education theory, and discusses tensions and challenges in implementing them in the Soviet context.
Keywords: adult education; Nadezhda Krupskaya; political education; Soviet adult education